2023
DOI: 10.1111/rec.13867
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial lichen caribou forage transplant success: year 5 and 6 results

Abstract: The southern mountain caribou—a subpopulation of caribou found in British Columbia—is listed on Schedule 1 of the Federal Species at Risk Act as Threatened. Woodland caribou are diet specialists, relying on Cladonia subgenus Cladina lichen as a primary food source during winter months. Lichens are burned along with trees and other vegetation during stand‐replacing wildfire events, a natural disturbance in caribou ranges. In an attempt to accelerate the return of post‐fire forests to productive caribou winter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Our results are consistent with similar studies that found Cladonia spp. patch transplants survive 6 years post‐wildfire (Rapai et al 2023) and Nephroma articum lichen transplants can effectively acclimate to new environmental conditions (Sonesson et al 2007). Our findings suggest that transplanting lichen patches should be a suitable approach for maintaining lichen cover on rock barren landscapes, essential for primary soil formation and ecosystem succession, and for creating lichen‐dominated turtle nesting habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with similar studies that found Cladonia spp. patch transplants survive 6 years post‐wildfire (Rapai et al 2023) and Nephroma articum lichen transplants can effectively acclimate to new environmental conditions (Sonesson et al 2007). Our findings suggest that transplanting lichen patches should be a suitable approach for maintaining lichen cover on rock barren landscapes, essential for primary soil formation and ecosystem succession, and for creating lichen‐dominated turtle nesting habitat.…”
Section: Discussionmentioning
confidence: 99%